Kekuatan Hukum Kartu Keluarga Bagi Pasangan Nikah Tidak Tercatat (Analisi Perlindungan Terhadap Hak Perempuan) - Alex Zainul Hasan (SAKINAH: Jurnal Hukum Keluarga Islam, 2026)
This research aims to analyze the legal validity of family cards (KK) for couples with unregistered marriages and to assess whether the inclusion of the note “unregistered marriage” on the family card fulfills the principle of legal protection for women. This issue arises from the implementation of Minister of Home Affairs Regulation (Permendagri) No. 108 of 2019, which allows couples with unregistered marriages to obtain a family card by signing a Statement of Absolute Responsibility (SPTJM). Although this regulation provides an administrative solution, it also creates legal uncertainty regarding marital status and women’s protection. The research uses a normative legal research method with statutory, conceptual, and comparative approaches. The data sources consist of primary and secondary legal materials collected through library research, analyzed qualitatively through several stages—identifying legal facts, examining applicable norms, and drawing conclusions based on the principle of legal protection. The results show that the family card for couples with unregistered marriages only provides administrative recognition, granting access to public services such as education and healthcare but not altering the legal status of the marriage, as it lacks formal registration required under Law No. 1 of 1974 on Marriage. In terms of legal protection, the inclusion of “unregistered marriage” offers advantages by providing administrative acknowledgment of women’s and children’s status; however, it still poses legal uncertainty in proving rights to inheritance, joint property, and protection from domestic violence. Therefore, although administratively beneficial, this policy has not yet fully ensured comprehensive legal protection for women.